Ответы и объяснения

Лучший Ответ!
2012-02-14T19:01:01+04:00

cos(2x)-cosx=0

cos^2(x)-sin^2(x)-cosx=0

cos^2(x)+cos^2(x)-1-cosx=0

2cos^2(x)-cosx-1=0

cos^2(x)=t, то

2t^2-t-1=0

D=1+8=9

x1=(1+3)\4=1                                                    x2=(1-3)\4=-1\2

cosx=1                                                              cosx=-1\2 

x=Pi + Pi*n, где n принадлежит Z                       x=(Pi-(Pi\3))+(2Pi*n)

                                                                         x=2Pi\3+(2Pi*n), n принад Z

   Ответ: 2 выражения конечных